Pinecone 1987 - Valdosta State College (Valdosta State College, 1987)
June 87 MILESTONES Beach Boys Bring Endless Summer To VSC. Halloween, a time for ghosts and goblins to air out their dirty linens, brought ghoulish fun to the P.E. Complex as America's oldest teenagers. The Beach Boys, celebrated their 25th anniversary at Valdosta State. The Original Shrink-To-Fit 501 Blues. Pace 4 For more than 125 years America's favorite jeans, the ones that shrink-to-fit, have riveted pockets, and a button-fly, are still the best. They are, of course, Levi's 501s....
Milestones 1987
A year book was published for Valdosta State College from 1925-1977, under the name The Pinecone. From 1981-1987, a yearbook was published called Milestones. Valdosta State University had three names during this period, Georgia State Womans College, 1925-1950; Valdosta State College, 1950-1993; and Valdosta State University 1993-present.
Keywords: yearbook; University History; Americana